ANALISIS PERCABANGAN RETAK PADA MATERIAL KERAMIK PIEZOELEKTRIK - Puja, IGN Wiratmaja; Hidayat, Muhamad; Qin, Qing Hua (Mesin, 2005)
Crack branch or kink in piezoelectric body may occur due to mechanical or electric loading. This paper presents the analysis of crack branch for ceramic piezoelectric materials. This type of advanced materials is very advantageous for application in smart structures, measurements device and actuators. Utilizing the extended Stroh Formalism for elastoelectric, the boundary value problems are solved by way of Hilbert Transforms. The explicit expressions for the elastic, electric, stress and electric intesity factor, and strain energi density are presented in integral forms. These integrals are solved using Gauss-Chebysev-Quadrature. Numerical results for piezoelectric ceramics are presented to illustrate both qualitative and quantitative behaviour of the stress- electric intesity factors.